Jam’ al-Quran pada Masa Nabi Muhammad SAW dan Khulafaurasyidin - Putri M, Amalia Undip (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
For more than 1400 years, the Quran has maintained it’s authenticity. The reason is inseparable from the role of the Prophet Muhammad and his compainons in maintaining the originality of the Quran. The method used in this research is qualitative library research with a historical approach. Primary data was in the form of references that do not specifically discuss about Jam’ul Qur’an. Data were collected by orientation and exploration methods. Then data were analyzed using inductive techniques. The results showed that the Jam’ul Qur’an at the time of the phophet Muhammad SAW was done by memorizing and writing it in fragments. At the time of Abu Bakr it was made into a manuscript called the Mushaf of Abu Bakr. Lastly, the Usman period of the Qur’an was made into a new mushaf with the mushaf qiraat standard which was mutawatir from Rasulullah SAW, than it was reproduced and sent to all Islamic territories as a basis for teaching the Qur’an. The thee periods of the Jam’ul Qur’an being carried out. Keywords: The Jam’ul Qur’an. Muhammad SAW, Khulafaurashidin.